Five Centuries of Glory: The North-South Colonnaded Street of Sagalassos in the First and the Sixth Century A.D. - Jacobs, Ine; Waelkens, Marc (Istanbuler Mitteilungen, 2024)
Excavations undertaken between 2005 and 2009 on the north-south Colonnaded Street of Sagalassos (southwest Turkey) have provided valuable information concerning the very early, Tiberian, planning and creation of such a street in Asia Minor. Moreover, after having functioned as the backbone of the town for almost five centuries, the street was thoroughly renovated. Its colonnades were reconstructed, the pavement repaired, a new staircase and a street fountain were installed, and a new statuary display was created. As such, it is also a rare example of a highly representative, sixth-century colonnaded street, as well as one of the last major civic undertakings in the entire Eastern Mediterranean. This article reconstructs the main building phases of the Colonnaded Street at Sagalassos in detail and puts them into context by comparing them with contemporaneous undertakings in and outside of Asia Minor.